The effects of sales growth, leverage, and firm size on tax avoidance: Evidence from Indonesian manufacturing companies, 2021–2025 - Ratu Anggi Triani; Febby Febriana; Indra Sulistiana (International Journal of Applied Finance and Business Studies, 2026)
Corporate tax avoidance remains relevant in Indonesia because low effective tax payments may weaken fiscal capacity, particularly when firms face financing and recovery pressures. This study examines the associations of sales growth, leverage, and firm size with the cash effective tax rate (CETR) of manufacturing firms listed on the Indonesia Stock Exchange. The final balanced sample comprises 10 firms and 50 firm-year observations for 2021–2025, selected through purposive screening for continuous listing, complete annual reports, and complete inputs for all variables. CETR is measured as cash taxes paid divided by profit before tax; therefore, a lower CETR indicates greater tax avoidance, whereas a higher CETR indicates lower tax avoidance. The available estimates were generated using pooled ordinary least squares as a baseline specification. Sales growth is negatively but not significantly associated with CETR (β = −0.142; p = 0.085), while leverage (β = 0.017; p = 0.012) and firm size (β = 0.013; p = 0.017) are positively associated with CETR. The model is jointly significant (F = 6.252; p = 0.001) and explains 29.0% of CETR variation (adjusted R² = 0.243). Because the dependent variable is CETR, the positive leverage and firm-size coefficients indicate higher cash tax rates and therefore lower—not higher—tax avoidance. Practically, tax authorities should prioritize persistent low-CETR patterns and the substance of financing arrangements rather than treating high leverage or large firm size as automatic evidence of avoidance. The contribution lies in clarifying the inverse interpretation of CETR and reassessing mixed evidence during the pandemic and early recovery period. Nevertheless, the small sample, detected heteroskedasticity, absence of fixed- or random-effects estimation, and lack of an ETR robustness test require cautious interpretation.